The Prevalence of Factor XII Deficiency in 103 Orally Anticoagulated Outpatients Suffering from Recurrent Venous and/or Arterial Thromboembolism - Halbmayer, Walter-Michael; Mannhalter, Christine; Feichtinger, Christine; Rubi, Karl; Fischer, Michael (Thrombosis and Haemostasis, 1992)
One hundred and three patients suffering from recurrent venous thrombosis, recurrent arterial thromboembolism and/or recurrent myocardial infarction and 50 healthy subjects were tested for Hageman factor (FXII) coagulant activity and antigen. Among the 103 patients we identified 15 subjects with FXII deficiency (15%), 3 with protein C deficiency (3%) and 3 with protein S deficiency (3%). Combined FXII and protein C, protein S or antithrombin III deficiency was not observed. The 103 patients were devided into subgroups according to the type of thrombotic complication. Among patients with exclusively recurrent venous thromboembolism 8% (p = 0.153) were deficient in FXII. Among patients suffering from recurrent arterial thromboembolism and/or myocardial infarction, the incidence of FXII deficiency was significantly higher (20%, p < 0.003). In 67% of the patients with FXII deficiency a positive family history of thrombosis could be established. In contrast, only 32% of all venous and 28% of all arterial thrombosis patients had a positive family history. We believe that reduced levels of FXII should be considered as a risk factor in the development of thromboembolism. Consequently, more attention should be payed to the measurement of FXII when evaluating thromboembolic risk factors especially in cases of recurrent arterial thromboembolism and/or myocardial infarction.